EDUKASI KELOMPOK DIABETES MELITUS TENTANG TERAPI AKUPRESUR DI WILAYAH KERJA PUSKESMAS MARTAPURA 1 KABUPATEN BANJAR - fratama, ferry fadli; Prayogi, Bisepta; Apriansyah, Fajar; Shadrina, Aqiilah Nur; Rizqullah, Muhammad Yazid; Azlina, Noor Latifah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
The World Health Organization (WHO) reported that around 10.5% or 537 million people worldwide suffer from diabetes mellitus. According to RISKESDAS (2018), the prevalence of diabetes mellitus based on measurements of the Indonesian population is 1.5%, with South Kalimantan at 1.3%. The aim of this community service is to enhance the knowledge and skills of diabetes mellitus groups regarding diabetes management through acupressure at the Sanyinjiao acupoint and Zusanli acupoint. The implementation of this community service activity consists of two activities: the first activity is the formation of a healthy acupressure group, and the second meeting involves demonstrating acupressure at the Sanyinjiao acupoint and Zusanli acupoint. The outcome of this community service is an increase in knowledge and skills among diabetes mellitus groups in diabetes management. Keyword : diabetes melitus, acupressure, sanyinjiao acupoint, zusanli acupoint